Motor speech disorders in the nonfluent, semantic and logopenic variants of primary progressive aphasia. (July 2021) - Staiger, Anja; Schroeter, Matthias L.; Ziegler, Wolfram; Schölderle, Theresa; Anderl-Straub, Sarah; Danek, Adrian; Duning, Thomas; Fassbender, Klaus; Fliessbach, Klaus; Jahn, Holger; Kasper, Elisabeth; Kornhuber, Johannes; et al.
Abstract: Objective: Motor speech disorders (MSDs) are characteristic for nonfluent primary progressive aphasia (nfvPPA). In primary progressive aphasia (PPA) of the semantic (svPPA) and of the logopenic type (lvPPA), speech motor function is considered typically intact. However, knowledge on the prevalence of MSDs in svPPA and lvPPA is mainly based on studies with a priori knowledge of PPA syndrome diagnosis. This fully blinded retrospective study aims to provide data on the prevalence of all types of MSDs in a large sample of German-speaking patients with different subtypes of PPA. Method: Two raters, blinded for PPA subtype, independently evaluated connected speech samples for MSD syndrome and severity from 161 patients diagnosed with nfvPPA, svPPA or lvPPA in the database of the German Consortium of Frontotemporal Lobar Degeneration (FTLDc). In case of disagreement, a third experienced rater re-evaluated the speech samples, followed by a consensus procedure. Consensus was reached for 160 patients (74 nfvPPA, 49 svPPA, 37 lvPPA). Main results: Across all PPA syndromes, 43.8% of the patients showed MSDs. Patients with nfvPPA demonstrated the highest proportion of MSDs (62.2%), but MSDs were also identified in svPPA (26.5%) and lvPPA (29.7%), respectively. Overall, dysarthria was the most common class of MSDs, followed by apraxia of speech. In addition, we identified speech abnormalities presenting as "syllabic speech", "dysfluent speech", and "adynamic speech". Discussion: Our study confirmed MSDs as frequently occurring in PPA. The study also confirmed MSDs to be most common in patients with nfvPPA. However, MSDs were also found in substantial proportions of patients with svPPA and lvPPA. Furthermore, our study identified speech motor deficits that have not received attention in previous studies on PPA. The results are discussed against the background of the existing literature on MSDs in PPA, including theoretical considerations of the neuroanatomical conditions described for each of the different subtypes of PPA.